Role of receptor activator of nuclear factor-kappa B ligand (RANKL), osteoprotegerin and macrophage protein 1-alpha (MIP-1a) in monoclonal gammopathy of undetermined significance (MGUS) - Politou, M.; Terpos, E.; Anagnostopoulos, A.; Szydlo, R.; Laffan, M.; Layton, M.; Apperley, J.F.; Dimopoulos, M.-A.; Rahemtulla, A. (British Journal of Haematology, 2004)
The aim of this study was to evaluate the role of markers of bone remodelling, and osteoclast activation/function in patients with monoclonal gammopathy of undetermined significance (MGUS). We have measured serum levels of soluble RANKL (sRANKL), osteoprotegerin (OPG), macrophage inflammatory protein-1alpha (MIP-1α), markers of bone resorption [N-telopeptide of collagen type-I (NTX), and tartrate-resistant acid phosphatase isoform-5b (TRACP-Sb)] and bone formation [bone-alkaline phosphatase (bALP)] in 40 MGUS patients. These parameters were compared with those of 42 newly diagnosed myeloma patients, and 45 healthy, gender- and age-matched controls. MGUS patients had elevated levels of NTX, sRANKL, and sRANKL/OPG ratio compared with controls (P < 0.0001). Furthermore, TRACP-5b, MIP-1α and NTX were decreased in patients with MGUS compared with myeloma patients (P < 0.001), while OPG and bALP were increased (P < 0.001). Serum levels of MIP-1α, as well as TRACP-Sb, and sRANKL/OPG ratio were reduced, while bALP was increased in MGUS patients, even when compared with myeloma patients who had stage I/II disease. These results demonstrate that increased osteoclastogenesis leading to increased bone resorption is present in MGUS but seems to be compensated for by normal bone formation, which is absent in MM. Furthermore MIP-1α, bALP, and sRANKL/OPG may be useful tools for distinguishing between cases of MGUS and early myeloma.
Keywords: Macrophage inflammatory protein-1 alpha; monoclonal gammopathy of undetermined significance; multiple myeloma; Osteoprotegerin; Receptor activator of nuclear factor-kappa B ligand